EFFECT OF EMPLOYEE DEVELOPMENT AND TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Irawati; Salju; Goso; Rahmawati; Rismawati, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study investigates the impact of Employee Development and Transformational Leadership on Employee Performance, with Organizational Commitment serving as a mediating variable. The research was conducted among employees in the East Luwu Regency Government, focusing on how these key factors interact to influence performance outcomes. The novelty of this study lies in its comprehensive examination of Organizational Commitment as a pivotal mediator that enhances the effects of leadership and development practices on employee performance. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study revealed that Transformational Leadership significantly boosts Organizational Commitment, which in turn, has a strong positive effect on Employee Performance. However, Employee Development's direct impact on performance was not significant, indicating that its influence is mediated through Organizational Commitment. These findings underscore the importance of fostering a supportive leadership environment and investing in development programs that cultivate commitment to drive higher performance.